Hubungan Kelas Sosial Orang Tua Siswa dengan Hasil Belajar Siswa Madrasah Ibtidaiyah At-Taqwa 51 Bekasi - Moh. Gumelar Alam; Henri Peranginangin; Iis Humaeroh (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Children have different morals and personalities depending on their upbringing. This can affect student learning outcomes, researchers suspect that low and high learning outcomes there is a tendency towards the social class of students' parents. The purpose of this study was to determine the relationship between the social class of students' parents and the learning outcomes of class VI students at Madrasah Ibtidaiyah At-Taqwa 51 Bekasi. This study uses a quantitative approach to personal correlation to determine the relationship between the two variables by distributing in-depth questionnaires to parents of students at Madrasah Ibtidaiyah At-Taqwa 51 Bekasi, totaling 60 respondents. Based on the results of the statistical test of the research hypothesis using pearson correlation, the Alpha Sig value was obtained. 0.000 <0.05, which is equal to 0.000 <0.05 or with the test results using rcount > rtable of 0.486 > 0.254 so that H0 is rejected and Ha fails to reject. It can be concluded that there is a significant relationship between the social class relationship of parents and the learning outcomes of class VI students at Madrasah Ibtidaiyah At-Taqwa 51 Bekasi with a correlation magnitude of 23%. So these results indicate that parents' income has a relationship with student learning outcomes, the higher the social class of parents will have an impact on improving student learning outcomes.